2021
DOI: 10.1038/s41380-021-01027-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, brain, and intelligence differences

Abstract: Individual differences in human intelligence, as assessed using cognitive test scores, have a well-replicated, hierarchical phenotypic covariance structure. They are substantially stable across the life course, and are predictive of educational, social, and health outcomes. From this solid phenotypic foundation and importance for life, comes an interest in the environmental, social, and genetic aetiologies of intelligence, and in the foundations of intelligence differences in brain structure and functioning. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 146 publications
8
85
0
6
Order By: Relevance
“…Similar to mutualism theory, P-FIT theory stresses the importance of local interactions, be it between brain regions rather than psychological processes. Their idea resonates with other neuroscientists, evidenced by the various compatible theories introduced in recent years (for brief summaries, see Barbey, 2018;Deary et al, 2021).…”
Section: Mutualismsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar to mutualism theory, P-FIT theory stresses the importance of local interactions, be it between brain regions rather than psychological processes. Their idea resonates with other neuroscientists, evidenced by the various compatible theories introduced in recent years (for brief summaries, see Barbey, 2018;Deary et al, 2021).…”
Section: Mutualismsupporting
confidence: 55%
“…At large, the mechanisms that drive human intelligence remain a mystery (e.g., Deary et al, 2021). However, some mechanisms have been identified that likely play a role in producing some of its phenomena.…”
Section: Mechanismsmentioning
confidence: 99%
“…Genetic propensity to higher educational attainment may include variants that promote optimal cortical development. The cellular processes underlying developmental changes in SA, including synaptic function, have been associated with genes linked with the significant SNPs identified in GWAS of educational attainment (Deary et al, 2021; Okbay et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Utilising 10 years of research on genetics, intelligence and brain imaging, Deary, Cox and Hill examine genetic correlations of intelligence and measurements of brain volume, including 'intracranial volume, total brain volume, grey matter volume, white matter volume, and volume of the left posterior cingulate cortex' (Deary, Cox & Hill 2021).…”
Section: Genetic Enhancements Intelligencementioning
confidence: 99%